Respostas
respondido por:
1
Olá, Edney. (=^.^=)/
{ - 20 + ( - 7 + 9 )^3 - [ - 7 + 9 - ( - 1 + 5 ) ] - ( - 1 )^3}
{-20+(2)^3-[-7+9-(4)]-(-1)} =
{-20+8-[-7+9-4]+1} =
{-20+8-[-11+9]+1} =
{-20+8-[-2]+1} =
{-20+8+2+1} =
-20+11 = -9
Conte sempre comigo.
Bons estudos! :-D
{ - 20 + ( - 7 + 9 )^3 - [ - 7 + 9 - ( - 1 + 5 ) ] - ( - 1 )^3}
{-20+(2)^3-[-7+9-(4)]-(-1)} =
{-20+8-[-7+9-4]+1} =
{-20+8-[-11+9]+1} =
{-20+8-[-2]+1} =
{-20+8+2+1} =
-20+11 = -9
Conte sempre comigo.
Bons estudos! :-D
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás